2015
DOI: 10.2134/agronj15.0186
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Biomass Production and Water Use in the Central Great Plains

Abstract: The water‐limited environment of the semiarid Central Great Plains may not produce enough cover crop biomass to generate benefits associated with cover crop use in more humid regions. There have been reports that cover crops grown in mixtures produce more biomass with greater water use efficiency than single‐species plantings. This study was conducted to determine differences in cover crop biomass production, water use efficiency, and residue cover between a mixture and single‐species plantings. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
123
5
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 40 publications
(48 reference statements)
10
123
5
5
Order By: Relevance
“…The total plant available soil water in the soil profile (0-240 cm) was calculated as sum of the available water values measured by 30 cm increments. Crop water use was calculated by water balance method-summing soil water depletion (soil water near planting minus soil water after harvest) plus in-season precipitation similar to Nielsen et al (2015). Deep percolation and runoff were not measured and assumed to be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…The total plant available soil water in the soil profile (0-240 cm) was calculated as sum of the available water values measured by 30 cm increments. Crop water use was calculated by water balance method-summing soil water depletion (soil water near planting minus soil water after harvest) plus in-season precipitation similar to Nielsen et al (2015). Deep percolation and runoff were not measured and assumed to be negligible.…”
Section: Methodsmentioning
confidence: 99%
“…Cover crops (CCs) have been increasingly considered for improving soil health and agroecosystem sustainability across the US in recent years. However, improvements in SOC storage and soil health due to CC are primarily observed in areas where water is not a limiting factor for crop production [3]. In the drylands of the Southern High Plains region of the US, SOC cycling is primarily limited by biomass carbon inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of legumes in an annual grass mixture also did not increase forage mass production in winter cover production (Lithourgidis et al, 2006). Other studies have also found that legumes contribute a small portion of the total forage mass in mixtures in spring‐planted cover crops (Nielsen et al, 2015a; Nielsen et al, 2015b). Overall, legumes offer such a small contribution to forage mass production compared with brassicas and grass species that even if they were planted at a higher proportion of the mixture, overall forage mass production would not be significantly impacted.…”
Section: Legume Productionmentioning
confidence: 90%